Український релігійно-етичний Еґо-концепт у дискурсі «Саду божественних пісень» Григорія Сковороди – Івана Карабиця - Драганчук, Вікторія Миколаївна; Drahanchuk, Viktoriia M.; Драганчук, Виктория Николаевна (Тернопільський національний педагогічний університет імені Володимира Гнатюка, 2016)
Проаналізовано втілення українського Еґо-концепту у творі І. Карабиця, що реалізує Сковородинський сенс життєтворчості – від “материнської землі”, через життєві хвилювання, до веселості Серця і перебування у Бозі. Відзначено символіку ліричного тенора як архетипу національного співу і асоційованої з філософом флейти-сопілки. Indeed correct development strategies of the state, without exaggeration, are formed in its spiritual sphere, which determines the development of all other areas of society. What a nation tends actually that it gets in end. Ukraine has an invaluable treasure; it is a reflection of the divine Word in the light of their own mentality, their collective inner “I”. It made by the “lover of the Holy Bible” from cossack family Hryhoriy Skovoroda. Displaying of Ukrainian Ego-concept as Skovoroda’s metaphysical vision through the prism of Baroque musical discourse by Ivan Karabytz is analysed in the article. The composer constructed the dramatic line in a similar way to Skovoroda’s meaning of life making, from “maternal earth” through stormy excitement in life sea, to “Heart gladness” and to being in God. The symbols of lyric tenor as “the national vocal singing archetype” (I. Prystalov) and associated with the philosopher flute-panpipe is noted during this study. I. Karabytz referring to Skovoroda’s poetry updates the genre of partesny concert, embodying its meaning in a modern style and continuing the tradition of “high” Baroque of Mykola Dyletzky and of the “golden age” of choral concert. This is reflected in contrasting comparison of parts (six parts of the concert are complex a binary form) and in using of certain features (but not the entire structure) as diatonic, episodic a cappella, especially the choral texture, polyphony and more. In general, see the intonational influences of choral chant in polyphony and folk singing in soprano, the combination of monodical, harmonic and polyphonic compositions, and the principles of modal and tonal thinking. The prologue of the concert symbolizes Ukrainian cardiocentrism. Composer uses the tenor’s solo performing 13th song “Ah field, green field...” what echoes the “Song of Songs” by Solomon. Prologue shows a mother earth, small motherland, everyone saves cordial relationship and heartfelt unity with its nature. The work pans used the famous chant “For everybody town a temper and rights...” It was a philosophical parable about the possibility of spiritual immortality, the only way in which is crystal purity of conscience. The first lines are voiced tenor and bass duet, in which quasiizorytmic sound along with the octave, quint appear harsh dissonances that conjures grotesque “grassroots” baroque. In the final which is a clear imitation of partesny concert a cappella the choir sings solemnly the answer to the main question of the life meaning in light catharsis sounding: “The heart gladness is a pure light...” At the end the pastoral flute-panpipe melody sounds, it personified the philosopher Hryhoriy Skovoroda who knew the divine in yourself. It is a first Neobaroque concert in Ukrainian music.
The Ukrainian religious and ethical Ego-concept in discourse of “The garden of the Devine songs” by Hryhoriy Skovoroda– Ivan Karabytz
Украинский религиозно-этический Эго-концепт в дискурсе “Сада божественных песней” Григория Сковороды – Ивана Карабица
Keywords: Сковородинський архетип; веселість серця; необароковий концерт; партесний концерт; музична традиція; Skovoroda’s archetype; gladness of heart; Neobaroque concert; partesny concert; music tradition; Сковородинский архетип; весёлость сердца; необарочный концерт; партесный концерт; музыкальная традиция